2014
DOI: 10.1097/scs.0b013e3182a2eddd
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume Levels in Children With Adenoid Hypertrophy

Abstract: Adenoid hypertrophy (AH) is a common disorder in children, resulting in chronic nasal congestion. This chronic congestion should be evaluated carefully because it can lead to chronic upper airway obstruction. Many authors have suggested that increased nasal resistance to respiration may cause disturbances in the pulmonary ventilation and carry the risk of cardiopulmonary diseases. Mean platelet volume (MPV) is a marker of platelet function and is positively associated with indicators of platelet activity. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Kucur et al [17] observed statistically higher MPV levels in children with adenoid hypertrophy. In contrast, Cengiz et al [10] found statistically lower MPV levels in children with chronic tonsillitis and adenoid hypertrophy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Kucur et al [17] observed statistically higher MPV levels in children with adenoid hypertrophy. In contrast, Cengiz et al [10] found statistically lower MPV levels in children with chronic tonsillitis and adenoid hypertrophy.…”
Section: Discussionmentioning
confidence: 95%
“…[13][14][15][16] There are limited studies pointing to the association between adenoid hypertrophy and MPV in pediatric OSAS. [10,17] However, to our knowledge, there is no study in the literature dealing with the association between pediatric OSAS and MPV/PC. In the present study, the association between OSAS caused by adenotonsillar hypertrophy and MPV and MPV/PC ratio in children with OSAS diagnosis was studied and the impact of adenotonsillectomy on these two parameters was evaluated.…”
mentioning
confidence: 99%
“…Sagit et al [9] found that septoplasty has a curative effect for hypercoagulopathy with reducing MPV values. Kucur et al [25] found that MPV values were found to be higher in children with AH than controls and there was a significant reduction in MPV levels after adenoidectomy. They demonstrated that MPV levels may indicate the risk of cardiopulmonary diseases.…”
Section: Discussionmentioning
confidence: 96%
“…In literature, there have been few studies of exploring the relationship between MPV and AH [12]. MPV levels show indirectly the cardiopulmonary risks and morbidity.…”
Section: Discussionmentioning
confidence: 99%